Survival of cervical cancer patients and its prognostic factors at Cipto Mangunkusumo Hospital, Jakarta (Medical Journal of Indonesia, 2014)
Background: Cervical cancer is the second most common cancer among Indonesian women. Information concerning survival probability is very important for the patient and institution. Our last data about cervical cancer survival was studied for more than 10 years ago. This study aimed to know the latest cervical cancer survival and its prognostic factors.Methods: This is a retrospective cohort study which enrolled cervical cancer patients treated at Cipto Mangunkusumo Hospital in 2005-2006. Subjects were followed-up for minimum of 5 years. Kaplan-Meier and Cox regression analysis was used to determine the survival probability and to assess prognostic factors. Results: A total of 447 patients who met the study criteria were selected. Stage III was the largest proportion on the study (41.6%). Most of the histopathology type was squamous cell carcinoma (71.6%). This study revealed that median survival was 63 months with the overall 5-years survival probability to be 52%. Tumor size did not influence overall survival rate. Stage III and IV had lower survival probability (HR 3.27 and 6.44). Poor differentiation and uncompleted therapy also had lower survival probability (HR 2.26 and 2.22). Histopathology of others (neuroendocrine) had lower survival probability (HR 2.85). However, it was not statistically significant on multivariate analysis. Conclusion: Median survival time for cervical cancer patients at Cipto Mangunkusumo Hospital was 63 months. There were improvement in the survival rate comparing from the study in 1997. In this study, the independent prognostic factors for survival were tumor staging, tumor differentiation, and completion of therapy.